DEVELOPMENT OF AN INDEX TO ASSESS THE BRAND IMAGE OF TOURIST DESTINATIONS - Varela Mallou, Jesús; García Carreira, Alberto; Manzano Arrondo, Vicente; Rial Boubeta, Antonio (Anales de Psicología / Annals of Psychology, 2006)
A destination’s image constitutes a central factor in the different models that analyze travel decision-making and its selection (Moutinho, 1984; Chon, 1990; Baloglu & McCleary, 1999). The studies consulted suggest that destinations with a positive image will have a higher probability of being considered and finally chosen in the selection process. The aim of this study is to propose a methodology for measuring brand image as an entirely psychological construct, deriving from the subjects’ perceptions of its component attributes. To develop and evaluate this measure, we analyzed the results of a survey of 916 tourists.